Structural Foundation Designers' Manual. - Curtin, W. G. (John Wiley & Sons, 2008)
This manual for civil and structural engineers aims to simplify as much as possible a complex subject which is often treated too theoretically, by explaining in a practical way how to provide uncomplicated, buildable and economical foundations. It explains simply, clearly and with numerous worked examples how economic foundation design is achieved. It deals with both straightforward and difficult sites, following the process through site investigation, foundation selection and, finally, design. The book:.:.; includes chapters on many aspects of foundation engineering that most other books avoi.